2021
DOI: 10.1007/s11864-021-00836-1
|View full text |Cite
|
Sign up to set email alerts
|

Models of Integration of Specialized Palliative Care with Oncology

Abstract: Opinion statement Evidence from randomized controlled trials and meta-analyses has shown that early integration of specialized palliative care improves symptoms and quality of life for patients with advanced cancer. There are various models of early integration, which may be classified based on setting of care and method of palliative care referral. Most successful randomized controlled trials of early palliative care have used a model of specialized teams providing in-person palliative care in free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 96 publications
1
43
0
1
Order By: Relevance
“…In line with the results reported by Mathews et al [97], where the integration of specialized palliative care with oncology patients was analysed, health professionals agreed that integrated PC services are the desired care models to facilitate integration and coordination of care using an interdisciplinary approach [74,77,78]. This study also highlighted the need to allocate more personnel, time, and training to assessing and addressing the needs of oncological patients and their families or caregivers, as identified in our review.…”
Section: Discussionsupporting
confidence: 88%
“…In line with the results reported by Mathews et al [97], where the integration of specialized palliative care with oncology patients was analysed, health professionals agreed that integrated PC services are the desired care models to facilitate integration and coordination of care using an interdisciplinary approach [74,77,78]. This study also highlighted the need to allocate more personnel, time, and training to assessing and addressing the needs of oncological patients and their families or caregivers, as identified in our review.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, a randomized trial showed QoL improvement and survival prolongation with early palliative care for stage IV NSCLC patients 4 . Nonetheless, while referral to palliative care after a diagnosis of metastatic NSCLC may be helpful in the management of symptom and side effects, this strategy is not feasible in broader practice due to the limited availability of specialized palliative care services (especially in lower resource settings), as well as patient/ provider hesitancy for early involvement 31,32 . Instead, clinician-initiated palliative referrals guided by institutional criteria, and/or identification of patients who may best benefit on the basis of symptom burden thresholds warrants additional evaluation 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a randomized trial showed QoL improvement and survival prolongation with early palliative care for patients with stage IV NSCLC [4]. Nonetheless, although referral to palliative care after a diagnosis of metastatic NSCLC may be helpful in the management of symptom and side effects, this strategy is not feasible in broader practice owing to the limited availability of specialized palliative care services (especially in lower resource settings), as well as patient/provider hesitancy for early involvement [31,32]. Instead, clinician-initiated palliative referrals guided by institutional criteria and/or identification of patients who may best benefit on the basis of symptom burden thresholds warrants additional evaluation [31].…”
Section: Discussionmentioning
confidence: 99%